2020
DOI: 10.1186/s41606-019-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of self-care for sleep disturbances: prevalence, profile, motivation, perceived effectiveness and medical provider communication

Abstract: Objective: This study aims to undertake the first critical review of self-care use among adults with sleep disturbances by focusing on the prevalence of self-care-the self-determined and self-administered use of products or practices-by adults with sleep disturbances. Methods: A comprehensive search of 2006-2016 international literature in CINAHL, AMED, Medline and EMBASE databases was conducted. The search was confined to empirical research findings regarding sleep disturbances -as indicated by a validated sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Meredith and colleagues performed a critical review of literature regarding patients with sleep disturbances and self-care and found that the use of maladaptive coping mechanisms was common in this population. 14 Limitations. The study had signifi cant limitations.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meredith and colleagues performed a critical review of literature regarding patients with sleep disturbances and self-care and found that the use of maladaptive coping mechanisms was common in this population. 14 Limitations. The study had signifi cant limitations.…”
Section: ■ Discussionmentioning
confidence: 99%
“…While there were limited studies to review, our findings supported those of other researchers on this topic. Meredith and colleagues performed a critical review of literature regarding patients with sleep disturbances and self-care and found that the use of maladaptive coping mechanisms was common in this population 14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes not only cause changes in the mechanism of depression and anxious behavior but causes sleep disorder. All these changes in the GABA receptors are induced by the sedative-hypnotic effects of some drugs [41].…”
Section: Methodsmentioning
confidence: 99%